Cultural relations in the global community problems and prospects - Bickley, Verner Courtenay; Philip, Puthenparampil John 1916-. (New Delhi Abhinav, 1981)
Outcome of a conference on "Emerging Issues in Cultural Relations in an Interdependent World", held in Honolulu, 1976.
The world as a system--a framework for thinking / Everett Kleinjans -- A quadrangular model : new perspectives of interdependence and conditions for Third World horizontal cooperation / Juan J. Valenzuela-Fuenzalida -- Prescriptions for paralysis : implications of determinism for cultural relations policy / Philip E. Jacob -- Alternative scenarios for developing countries / Dudley Seers -- Social and cultural implications of energy policies / Verner C. Bickley ... [et al.] -- Voluntary action and economic development in Third World countries / John G. Sommer -- Disengagement or cooperation in the social sciences / Krishna Kumar -- Research and development : with special attention to international linkages in higher education / Fred H. Harrington -- Cultural relativism and "parity of esteem" : test case in an African elite / Lemuel A. Johnson -- Cultural differences and world order / Ali A. Mazrui.
Includes bibliographical references and index.
Keywords: Cultural relations; International cooperation; Intercultural communication; Cultural relativism; Economic development